Trophic structure and interactions in Lake Ayamé (Côte d'Ivoire) - A. Traore; A. Ouattara; L. Doumbia; L. Tah; J. Moreau; G. Gourène (Knowledge and Management of Aquatic Ecosystems, 2008)
The Ecopath software with Ecosim and Ecospace was used to describe structure and trophic relationships in Lake Ayamé. The total biomass of fish is 8 t.km-2. The trophic levels assessment revealed that the highest value (3.83) was observed in Hepsetus odoe. The mean trophic level of catch (2.94) indicates that fisheries are targeting mainly the fish groups of high trophic levels. Resources are not exploited properly. Competition between species occurs for Sarotherodon melanotheron and Oreochromis niloticus for the first group and Chrysichthys spp. and Heterotis niloticus for the second group. Transfer efficiency is high from producers.